Enhancing Nursing Careers: The Role of Training and Work Environment Through Clinical Competence in X Sukabumi Hospital - Simarmata, Tioma Lusi Septiana; Indrawati, Ratna; Johanes, Johanes (Alta Dharma Publisher, 2025)
Background: Career development for healthcare professionals, particularly nurses, is a crucial aspect of Human Resource Management (HRM) in hospitals. At X Sukabumi Hospital, only 1.8% of the 159 nurses successfully advanced in their careers, despite the majority having more than 10 years of experience. Objective: This study examines the impact of training and work environment on nurses' career development, with clinical competence as a mediating variable. Method: A quantitative associative design with a cross-sectional approach was employed, using a questionnaire for data collection. The sample consisted of 159 nurses, and data were analyzed using the Three-Box Method and Structural Equation Modeling (SEM) with PLS v.03, incorporating T-tests and F-tests. Result: findings reveal that training, work environment, and clinical competence significantly influence nurses' career development (F-statistic = 86.55 > F-table = 2.81). However, training alone does not directly impact career development (p-value = 0.309), while the work environment has a significant effect (p-value = 0.000). Both training and work environment significantly influence clinical competence (p-value = 0.000), which in turn positively affects career development (p-value = 0.009). Furthermore, clinical competence plays a key mediating role (p-value= 0.018). Conclusion: In conclusion, training and work environment influence nurses' career development through clinical competence at X Sukabumi Hospital